International guidelines for self-report and proxy completion of paediatric health-related quality of life measures: a protocol for a systematic review - Julie Ratcliffe; Gang Chen; Kim Dalziel; Christine Mpundu-Kaambwa; Nancy Devlin (BMJ Open)
Introduction Measures of health-related quality of life (HRQoL), accompanied by the values (or utilities) required to estimate quality-adjusted life-years, are crucial for determining health benefits within economic evaluation and health technology assessment. Several generic and condition-specific measures or instruments of HRQoL, accompanied by values, currently exist for application with child populations. However, there is a lack of a structured summary of guidelines and recommendations for applying these measures in practice. This protocol describes a systematic review of guidelines and recommendations for child and proxy completion of child-specific measures of HRQoL. The aims of the review are to (1) identify and summarise published guidelines and recommendations for existing child-specific measures of HRQoL, (2) determine whether the identified guidelines and recommendations differ by instrument and child characteristics, (3) identify current gaps in these guidelines and recommendations and (4) identify best practices for child self and proxy assessment in paediatric HRQoL measurement for economic evaluation and health technology assessment.Methods and analysis The review will identify, collate and synthesise published guidelines and recommendations for existing child-specific utility measures of HRQoL. Electronic databases to be searched include the Cochrane Library, Medline, Scopus, Web of Science, EconLit, PsycINFO, CINAHL, Embase and Informit. The search will be extended to websites of (1) international organisations for health technology assessment, (2) regulation, health economics and HRQoL outcomes research and (3) instrument developers. Three reviewers will independently screen titles and abstracts against the inclusion criteria. A narrative synthesis will describe the key features of the guidelines identified.Ethics and dissemination Ethical approval is not required as the proposed systematic review will not use primary data. A paper of the systematic review will be submitted to a peer-reviewed journal for publication.PROSPERO registration number CRD42020207160.